Avaliação do ambiente da prática dos enfermeiros em oncologia. - ANDRADE, Bruna Rafaella Carvalho (2024)
Introduction: The professional practice environment is understood as a set of organizational attributes that facilitate or limit work. A favorable environment leads to greater professional satisfaction and involvement and consequently offers greater patient safety. Objectives: To evaluate the professional practice environment of nurses at a High Complexity Oncology Center in Maranhão. Methods: This is a cross-sectional study with a quantitative approach carried out with nurses from a High Complexity Oncology Center in Maranhão, in October and November 2023. A questionnaire was used to characterize the sociodemographic, economic and professional characteristics of the participating nurses, and a validated questionnaire called the Nursing Practice Work Environment Scale was used to evaluate the work environment, which may present favorable, unfavorable or mixed results. The data was analyzed using the IBM SPSS Statistics program. The Mann-Whitney, Kruskall-Wallis and for non-parametric tests to find correlations between the dimensions teste werw used Spearman. A significance level of 5% was considered. Results: The sample was made up of 57 nurses, with a predominance of females (77.2%), aged 30-34 (45.6%), self-declared brown race (47.4%), single marital status (50.9%), no children (47.4%), family income of more than 4 minimum wages (38.6%), with a postgraduate degree (73.7%), working in nursing for 10-13 years (31.6%). As for lifestyle habits, the majority said they practiced regular physical activity, did not use alcohol or tobacco, but 97.8% said they used coffee as a stimulant. With regard to the professional practice environment, all five dimensions, namely: participation in the institution's affairs, nursing fundamentals and quality of care, management skill and leadership, adequacy of human and material resources and interprofessional relations with doctors, were evaluated positively, with the final result being a favorable environment for professional nursing practice. Conclusions: The environment was evaluated as favorable for nurses to work in caring for cancer patients. It should be emphasized that tools that seek to verify professional satisfaction in their work environment are important for adjustments and planning, seeking better results in patient care, prioritizing the safety of the care provided.